2016
DOI: 10.1186/s13018-016-0380-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in carpal tunnel compliance with incremental flexor retinaculum release

Abstract: BackgroundFlexor retinaculum transection is a routine surgical treatment for carpal tunnel syndrome, yet the biomechanical and clinical sequelae of the procedure remain unclear. We investigated the effects of flexor retinaculum release on carpal tunnel structural compliance using cadaveric hands.MethodsThe flexor retinaculum was incrementally and sequentially released with transections of 25, 50, 75, and 100 % of the transverse carpal ligament, followed by the distal aponeurosis and then the antebrachial fasci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The mechanical properties of the TCL have been shown to vary with location. For example, cadaveric studies have found differences in the compliance of the proximal and distal TCL regions [36, 48], as well as differences in the elastic modulus [10] and amount of strain [3] between radial and ulnar ligament portions. Shear wave elastography methods, such as ARFI, provide a means to non-invasively quantify the elasticity of tissues in vivo , including those of the TCL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical properties of the TCL have been shown to vary with location. For example, cadaveric studies have found differences in the compliance of the proximal and distal TCL regions [36, 48], as well as differences in the elastic modulus [10] and amount of strain [3] between radial and ulnar ligament portions. Shear wave elastography methods, such as ARFI, provide a means to non-invasively quantify the elasticity of tissues in vivo , including those of the TCL.…”
Section: Discussionmentioning
confidence: 99%
“…The TCL has many biomechanical functions, including serving as an origin site for the thenar and hypothenar muscles [6, 8, 17, 39], stabilizing the carpal tunnel structure [4, 44, 48], acting as a pulley for the flexor tendons [14, 16], and contributing to carpal tunnel compliance [13, 19, 36]. Clinically, the TCL is closely associated with carpal tunnel syndrome (CTS) which is demonstrated by the ligament’s surgical transection as a common treatment to relieve median nerve compression within the carpal tunnel.…”
Section: Introductionmentioning
confidence: 99%
“…If data that includes different levels can be obtained from CTS patients and compared with a control group, much better information can be obtained. Fourth, the cause of CTS has multiple sources, including the transcarpal ligament, soft tissues, and flexor retinaculum [30,31]; however, we only focused on the median nerve. Fifth, because this study is not randomized and is a casecontrol group, an adjustment of baseline characteristics should be considered to compare the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical management of CTS involves transection of the flexor retinaculum to reduce compartmental pressure . It has been shown that complete transection of the flexor retinaculum is required to achieve maximum compliance of the carpal canal (ie, the greatest reduction in compartmental pressure) . Given the similarities between both syndromes in man and in horses, it could be concluded that release of a greater length of the deep metatarsal fascia should result in a greater reduction in compartmental pressure in horses with PSLD.…”
Section: Discussionmentioning
confidence: 99%